10 YEARS ON - HAS THE GOLD STANDARDS FRAMEWORK (GSF) INFLUENCED NURSING CARE OF PATIENTS WITH END OF LIFE CARE NEEDS IN THE COMMUNITY?. Issue 1 (1st March 2014) - Meehan, HC; Munday, D
Abstract : Introduction: District nurses (DN) play a key role in supporting patients with palliative care needs in the community. Gold Standards Framework (GSF) is a service improvement tool that was developed over 10 years ago for primary care, to enable GP practices to proactively support patients with palliative care needs. Aim(s) and method(s): This study explores the experiences of DNs working with practices that have implemented GSF and investigates their perceptions of how GSF has influenced provision of nursing care to patients with palliative care needs in the community. A qualitative methodology was used. Semi-structured interviews were undertaken with 8 DNs from one Trust. This Trust provided community nursing services to practices that had been early adopters of GSF. Results: The results identified a number of benefits and challenges for DNs in working with GSF practices. The benefits included early referral of patients to district nursing, proactive provision of supportive nursing care, team working, improved communication and improved recognition of the DN role in end of life care. Challenges included supporting practices with varying levels of GSF adoption, working with variability of engagement by GPs within a practice, supporting more patients with palliative care needs in the community, lack of continuity when working with external providers. Conclusion(s): There was evidence that GSF had influenced DN roles. There was evidence of an emerging advocacy role for GSF, the development of a nursing model using the principles of GSF to provide proactive nursing care to patients and empowerment of DNs to embed and sustain GSF within a local area.